Definisi Ekonomi Industri dan Masalah Ekonomi Industri - Dwi Arief Rahman; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Industrial economics is a part of economics that studies how the structure, behavior and results of industry. This article aims to understand the definition and problems in industrial economics by using a qualitative approach with literature studies. This study emphasizes the main problems of perfect competition, technological innovation, production efficiency, and government regulations that have an impact on industrial performance. By conducting a literature review, this study provides a conceptual overview that can be the basis for further research.